Assessment of Food Security Early Warning Systems for East and Southern Africa - Braimoh, Ademola; Manyena, Bernard; Obuya, Grace; Muraya, Francis (World Bank, Washington, DC, 2018)
The risk of the El Niño-induced food insecurity in southern Africa in 2016; the recent risk of famine in northern Kenya, Somalia, Ethiopia, and South Sudan; and the recent outbreak of the fall armyworm (FAW) in East and Southern Africa (ESA) all demonstrate that responses are still largely reactive than proactive. Inadequate early warning systems (EWSs), coupled with limited investment and weak institutional and technical capacity, are implicated in contributing to food insecurity–related emergencies in ESA. Yet over the years, strong evidence has emerged on the benefits of investing in EWSs. In Ethiopia, investing in a drought EWS, which would reduce livelihood losses and dependence on assistance, has a benefit-cost ratio (BCR) of between 3:1 and 6:1. Similarly, the BCR of improving national hydro-meteorological services in developing countries ranges from 4:1 to 36:1. Consistent with one of the goals of the Sendai Framework for Disaster Risk Reduction (SFDRR), increasing investment in EWSs would contribute to a substantial increase in the availability of, and access to multi hazard and disaster risk information, one of the key inputs in achieving the sustainable development goals (SDGs).